Cryptotanshinone mitigates ischemia reperfusion-induced testicular damage: A experimental study (Annals of Medical Research, 2021)
Aim: The aim of this study is to investigate the protective effects of cryptotanshinone on ischemia reperfusion-induced testis damage. Materials and Methods: In this study, the rats were divided into 3 groups. Groups of the study are planned as follows; sham, ischemia reperfusion, and ischemia reperfusion+cryptotanshinone. Oxidant molecules such as total oxidant status (TOS), malondialdehyde (MDA), myeloperoxidase (MPO) and antioxidant molecules like total antioxidant status (TAS), superoxide dismutase (SOD) with oxidative stress index (OSI) were evaluated in the testicular tissues obtained at the end of the experiment. Results: In ischemia reperfusion group, TAS and SOD levels decreased while other oxidant parameters were increased. But in ischemia reperfusion+cryptotanshinone group, the levels of anti¬oxidant parameters increased while the levels of oxidant parameters decreased. Conclusion: These results have shown us that cryptotanshinone is highly effective against oxidative testis damage caused by ischemia reperfusion.
Keywords: Testicular ischemia reperfusion; cryptotanshinone; oxidative stress; inflammation; rat.